A Panel Analysis of Trade Gravity between Pakistan and South Asian Countries - Waheed Ullah Jan; Mahmood Shah (Comparative Economic Research. Central and Eastern Europe, 2020)
This paper attempts to examinePakistan's trade patterns with South Asian countries by using a gravity model of trade. The main objective of the study is to quantify the long-run impacts of gravity variables. To achieve this objective, a panel data set for the period 2003 to 2017 has been used. Based on the mixed evidence of the results of panel unit root tests, Pooled Mean Group (PMG) and Panel Dynamic Ordinary Least Square (DOLS) techniques are applied. The outcome of the PMG and Panel DOLS models justifies the theoretical background of the gravity model and suggests that all the basic gravity variables haveusual signs. The RGDPs and population ofboth Paki- stan and the partner country have a positive impact on their bilateral trade. On the other hand,the distance between the two trading countries and the exchange rate have a negative impact on bilateral trade.The uniqueness of this study is that it measures the impacts of qualitative variables along with basic gravity variables. Language similarities and common borders have a positive impact on bilateral trade. Pakistan has borders with India and Afghanistan, but their trade relations are not worth men- tioning. The military conflicts between Pakistan and India, andthe political suspicions between Pakistan and Afghanistan hinder their trade relations.
Keywords: F12; F15; F42; F53; 330; South Asia; Pakistan; gravity model; exchange rate; population